Pengaruh Intellectual Capital terhadap Kinerja Keuangan dan Nilai Pasar Perusahaan - Melinda Haryanto; Henny - (Jurnal Manajemen Maranatha, 2013)
The objective of this study was to investigate influence of firm’sintellectual capital on their financial performance and market value. The objects of this paper are manufacturing industries listed at the Indonesian Stock Exchange period 2007 to 2008. By using 41 companies sample using purposive sampling method. This study used simple regression to examinethe influence intellectual capital (Value added intellectual capital (VAIC)) to financial performances and company market value. To examine the influence of three component of intellectual capital (capital employed efficiency(VACA), human capital efficiency (VAHU) and structural capital efficiency (STVA) to financial performances and company market value, this study uses multiple regression. The results showed that only VAHU has significant influence to company market value and only STVA has significant influenceto financial performance.